Membangun Persepsi Generasi Muda Dalam Menjaga Lingkungan Dengan Cara Literasi Think Green Dengan Komposter - Kustiyah, Elvi; Naidir , Ferra; Nuraliyah , Andi; Hasaya , Haudi; Ismaniah, Ismaniah (Universitas Islam Indonesia, 2024)
The importance of young people's awareness of the environment requires literacy or understanding how to treat waste. Our target is teenagers, so we chose Bina Karya Mandiri Bekasi Vocational School for this literacy, the accumulation of rubbish which causes environmental conditions to be less clean and will have an impact on health. This community service is carried out using a participatory training approach. Through waste management literacy by turning it into compost using the composter method, people can expand their knowledge and also provide solutions to existing problems. This literacy is carried out by holding seminars, providing facilities in the form of colored trash cans for sorting types of waste, as well as carrying out practices and assistance in making compost with a composter as a means of making compost at home at Binakarya Mandiri Vocational School Bekasi.